Comparative Study of Minimally Invasive Percutaneous Plate Osteosynthesis versus Reamed Intramedullary Nail Fixation for Extra Articular Distal Third Tibial Fractures - Shrestha, Dinesh Kumar; KC, Dipendra; Karki, Prateek; Shrestha, Sabin; Yogi, Sushil (Journal of Nepalgunj Medical College, 2021)
Introduction: Extraarticular distal third tibial fractures are highly controversial and difficult to treat despite of numerous methods of fixation. The most common methods of treating these fractures are minimally invasive percutaneous plate osteosynthesis (MIPPO) and reamed intramedullary nailing (RIMN). Aims: The aim of this study is to compare and assess its demographic status, preoperative status and functional outcomes of these two groups of patients with extraarticular distal third tibial fractures. Methods:This prospective hospital based observational study of 36 patients with extra articular distal third tibial fractures was carried out from January 2018 to January 2021 at Nepalgunj Medical College Teaching Hospital, Kohalpur. Thirty-six patients were included in the study and were divided into two groups of 18 each and were treated with MIPPO and RIMN methods and were followed up regularly. Clinical and functional outcome were evaluated at 12 months. Results: Out of 36 patients 20 were male and 16 were female. Mean age was 37.63with SD ± 11.43 years. Twenty two were right sided and 14 were left sided. Mean duration of surgery in MIPPO group was 75.33 with SD ± 14.64minutes and in RIMN group was 98.33with SD ± 18.96 minutes. There were 24 cases of associated fibular fractures. Two cases of surgical site infection and two cases of K-wire impingement on fibular side were encountered in MIPPO group whereas three cases of postoperative blisters were seen in RIMN group. All fractures united. The mean average time for fracture healing in MIPPO group was 25.55 weeks and in RIMN group was 27.55 weeks. The clinical and functional outcome were evaluated using American Orthopedic Foot and Ankle Society (AOFAS) scoring system, the mean score in MIPPO group was 91.22 and in RIMN group was 90.77. Conclusion: There was a good outcome in MIPPO group than RIMN group for extra articular distal third tibial fractures.